2011
DOI: 10.1007/s13353-011-0039-z
|View full text |Cite
|
Sign up to set email alerts
|

Species diversity of Trichoderma in Poland

Abstract: In the present study, we reinvestigate the diversity of Trichoderma in Poland utilizing a combination of morphological and molecular/phylogenetic methods. A total of 170 isolates were collected from six different substrata at 49 sites in Poland. These were divided among 14 taxa as follows: 110 of 170 Trichoderma isolates were identified to the species level by the analysis of their ITS1, ITS2 rDNA sequences as: T. harzianum (43 isolates), T. aggressivum (35), T. citrinoviride (11), T. hamatum (9), T. virens (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(86 citation statements)
references
References 48 publications
5
78
1
2
Order By: Relevance
“…Fifty-eight Trichoderma strains sourced from decaying wood, soil and mushroom farms in northern, eastern and central Poland had previously been identified by Błaszczyk et al (2011). Ninety Trichoderma isolates were collected from pieces of decaying wood in the forests of southern Poland (mountains) and isolated as described by Błaszczyk et al (2011).…”
Section: Fungal Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifty-eight Trichoderma strains sourced from decaying wood, soil and mushroom farms in northern, eastern and central Poland had previously been identified by Błaszczyk et al (2011). Ninety Trichoderma isolates were collected from pieces of decaying wood in the forests of southern Poland (mountains) and isolated as described by Błaszczyk et al (2011).…”
Section: Fungal Collectionmentioning
confidence: 99%
“…Mycelium for DNA extraction was obtained as described previously (Błaszczyk et al 2011). Isolation of total DNA was performed using the CTAB method (Doohan Volatile metabolite analyses by SPME GC-MS Trichoderma isolate preparation for solid-phase microextraction (SPME) sampling…”
Section: Molecular Analysismentioning
confidence: 99%
“…Accurate Trichoderma species discrimination can be done based on DNA sequence analysis of internal transcribed spacers (ITS) 1 and 2 of the rDNA gene cluster and fragments of the tef1, rpb2, chi18-5, and actin (act) or calmodulin (cal1) genes (Kindermann et al 1998;Dodd et al 2003;Jaklitsch et al 2006;Samuels et al 2006;Gal-Hemed et al 2011;Błaszczyk et al 2011;Atanasova et al 2013;Jaklitsch & Voglmayr 2015). The taxonomy of Trichoderma is continuously adjusted and updated (Jaklitsch 2011;Atanasova et al 2013;Jaklitsch & Voglmayr 2015;Chaverri et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, here and in a previous study, T. harzianum was the predominant taxon, T. harzianum is the most commonly reported species in the genus, occurring in diverse ecosystems and ecological niches. However, it must be borne in mind that the name "T. harzianum" applies to a species complex [31,32]. So we observed that most fusant strains trend to parent 1( T. harzianum NBAII Th 1) characters and these haplotype fusant species may be seen to comprise a multiplicity of species when subjected to multilocus phylogenetic analysis.…”
Section: Cluster Analysis Of Trichoderma Parent Strains and Their Fusmentioning
confidence: 79%